Xq28 duplications including MECP2 in five females: Expanding the phenotype to severe mental retardation - Bijlsma, E.K. (Elsevier, 2012)
Duplications leading to functional disomy of chromosome Xq28, including MECP2 as the critical dosage-sensitive gene, are associated with a distinct clinical phenotype in males, characterized by severe mental retardation, infantile hypotonia, progressive neurologic impairment, recurrent infections, bladder dysfunction, and absent speech. Female patients with Xq duplications including MECP2 are rare. Only recently submicroscopic duplications of this region on Xq28 have been recognized in four females, and a triplication in a fifth, all in combination with random X-chromosome inactivation (XCI). Based on this small series, it was concluded that in females with MECP2 duplication and random XCI, the typical symptoms of affected boys are not present. We present clinical and molecular data on a series of five females with an Xq28 duplication including the MECP2 gene, both isolated and as the result of a translocation, and compare them with the previously reported cases of small duplications in females. The collected data indicate that the associated phenotype in females is distinct from males with similar duplications, but the clinical effects may be as severe as seen in males.